The long-term relationship between capital and earnings in banking - Per Hortlund (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
Contrary to received wisdom, some recent studies report a negative relationship between leverage and profitability in banking in the 1980s and early 1990s. This study presents new data on the leverage and profitability of Swedish commercial banks in 1870-2001, and explores the sign of the relationship in the long term. In the studied period, the capital-asset ratio decreased by a factor four, while return-on-equity more than doubled. The leverage formula postulates a positive linear relationship between return-on-equity and the debt-equity ratio. A strong positive linear relationship was found over the period 1871-1980, but not in 1980-2001. Thus, while supporting the results of the previous studies, a long-term normal positive relationship between leverage and profitability is also reaffirmed.
Keywords: G21; N23; N24; 330; Return-on-equity; Leverage; Bank capital; Bank; Return on Investment; Betriebsergebnis; Kapitalstruktur